Social Engineering and the Legal Framework: Evaluating the Effectiveness of Drug Rehabilitation Policies in Promoting Socio-Economic Productivity - Wredha Danang Widoyoko; Siti Ngaisah; Haryono Haryono; Diah Ayu Rahmawati; Yoga Adi Prayogi (Westscience Press, 2024)
The interplay between social engineering and legal frameworks significantly influences the effectiveness of drug rehabilitation policies in fostering socio-economic productivity. This study employs a normative juridical approach to evaluate the alignment of existing laws and policies with the goals of societal reintegration and economic empowerment. Findings reveal that while some jurisdictions demonstrate success through integrated and holistic approaches, many face challenges such as stigma, insufficient funding, legal ambiguities, and fragmented systems. A comparative analysis highlights best practices from progressive models, emphasizing the importance of comprehensive legal frameworks, inter-agency coordination, and community-based support. Recommendations include strengthening anti-discrimination laws, integrating support systems, increasing funding, and promoting public awareness. This research underscores the potential of law as a tool for social engineering, providing actionable insights to enhance the socio-economic outcomes of drug rehabilitation policies.